2002
DOI: 10.1093/jn/132.7.2004
|View full text |Cite
|
Sign up to set email alerts
|

Methionine Supply to Growing Steers Affects Hepatic Activities of Methionine Synthase and Betaine-Homocysteine Methyltransferase, but Not Cystathionine Synthase

Abstract: The effects of supplemental methionine (Met), supplied abomasally, on the activities of methionine synthase (MS), cystathionine synthase (CS) and betaine-homocysteine methyltransferase (BHMT) were studied in growing steers. Six Holstein steers (205 kg) were used in a replicated 3 x 3 Latin square experiment. Steers were fed 2.6 kg dry matter daily of a diet containing 83% soybean hulls and 8% wheat straw. Ruminal infusions of 180 g/d acetate, 180 g/d propionate, 45 g/d butyrate, and abomasal infusion of 300 g/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 28 publications
6
23
2
Order By: Relevance
“…MTR activity was dramatically reduced when the cells were grown in Met+, although these conditions triggered maximal growth speed ( figure 1A and 3). Previous studies have already evidenced an influence of methionine on MTR activity [10,26,27]. Kamely et al observed an inhibitory effect of increasing concentrations of methionine on MTR activity of cells cultivated in presence of Hcy, Cbl and folates [10].…”
Section: Discussionmentioning
confidence: 96%
“…MTR activity was dramatically reduced when the cells were grown in Met+, although these conditions triggered maximal growth speed ( figure 1A and 3). Previous studies have already evidenced an influence of methionine on MTR activity [10,26,27]. Kamely et al observed an inhibitory effect of increasing concentrations of methionine on MTR activity of cells cultivated in presence of Hcy, Cbl and folates [10].…”
Section: Discussionmentioning
confidence: 96%
“…Frozen gut (jejunum and ileum) and liver tissues were homogenized (1:5, wt/vol) in 0.04 M potassium phosphate buffer (pH 7.5) containing 1 mM EDTA and 10 mM ␤-mercaptoethanol, as described by Lambert et al (20). Methionine synthase (MS) and cystathionine ␤-synthase (CBS) activities were determined as described previously (20) in the presence of 1 mM SAM for CBS activity assay (33).…”
Section: Enzyme Assaysmentioning
confidence: 99%
“…Data were normalized to 18S ribosomal RNA (⌬⌬Ct analysis). CBS activity was determined as described (18,46). Separate reactions were carried out in the presence and absence of 1.0 mM SAM to test for allosteric induction of CBS.…”
Section: Cbs Measurementmentioning
confidence: 99%